Fe-bearing MgSiO3 perovskite up to the Earth’s lower mantle conditions - Fang, Chanming; Ahuja, Rajeev (Física de la Tierra, 2012)
We investigated structural and electronic behaviors of Fe-MgSiO3 under pressure up to that in the Earth’s lower mantle using the first-principles theory. The Fe- MgSiO3 crystals have phase transform from the orthorhombic perovskite (OPv) structure into the orthorhombic post-perovskite (OPPv) phase and the transition pressure decreasing with increasing Fe concentration. Electronic transitions occur in the pressure range of about 70 to 90 GPa for an (Mg,Fe)(Si,Fe)O3 OPv crystal, in which the moment of the Fe4+ ion decreases gradually to zero at which the magnetic moment of the Fe2+ ion becomes zero. That electronic transition provides the possible mechanism to understand experiments.
Keywords: Fe-MgSiO3; pressure; Earth’s lower mantle; first-principles theory.